About Some Service Guns of the Hungarian Police – From a Different Point View - Regényi, Kund (Magyar Rendészet, 2022)
In 2020, the Hungarian Police started replacing its obsolete service handguns. Taking the opportunity, the article gives an overview of the major former service handguns of the Hungarian Police, presenting their advantages and disadvantages, searching for the reasons of their partial failure. The approach is less technical; in addition to outlining the political and economic background, the end-user experience is also presented. As a conclusion, the article welcomes the model replacement, mentioning some critical points as well.